Developing in vitro propagation systems for Curcuma sumatrana Miq.: a strategy for conserving and utilising an endemic sumatran wild-turmeric species - Apriliana Dyah Prawestri; Nada Maiza Arpita; Mimma Latifah Daraquthni; Annisa Putri Amalia Ma’ruf; Setia Nanda Ariana; Surya Diantina; Popi Aprilianti; Deritha Ellfy Rantau; Sitti Fatimah Syahid; Ratna Uli Damayanti Sianturi; Yosephin Martha Maria Anita Nugraheni; Marlina Ardiyani; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Digital twin-centered food safety management systems: A review of IoT, AI, and blockchain integration for bacterial pathogen control - Balarabe B. Ismail; Abdulrazaq Hassan Abba; Abdulrashid Ibrahim Sanka; Aliyu Idris Muhammad; Wenjun Wang; Donghong Liu (Food Research International, 2026)

Enhancing microbial safety and enzymatic stability of green peas using sequential sodium hypochlorite washing and continuous in-package DBD plasma treatment - Aliyu Idris Muhammad; Marlenne X. Atta-Delgado; Feihong Ji; Kevin M. Keener; Tian Ding; Xinyu Liao (Food Research International, 2026)

Widespread Use of Banned Pesticides and Weak Regulatory Enforcement: Environmental and Health Implications Among Farmers in Gombe State, Nigeria - Mohammad Bashir Sulaiman; Babangida Hammani; Abdullahi Muhammad Gimba; Oluyinka Omoyeni Akinlotan; Aliyu Tijjani Fadawa; Umar Musa Kwami; Taibatu Idris Umar; Amina Muhammad Bello (Journal of Agromedicine, 2026)

Mangrove Ecosystem Carbon Stocks: Insights from Setiu Lagoon, Malaysia - Mohammad Ahsanul Islam; Abu Hena Mustafa Kamal; Mohd Hanafi Idris; Md Masum Billah; AFM Arifur Rahman; Muhammad Shariefuddin Bin Mohd Sukeri; Md Khurshid Alam Bhuiyan (Estuaries and Coasts, 2026)

Red-edge versus traditional vegetation indices for detecting mangrove stress in Sumatera peat soils: Satellite-based evidence and policy implications from a tropical reserve forest - Muhammad Rendana; Efan Fatra Jaya; Febrian Hadinata; Puteri Kusuma Wardhani; Edward Saleh; Wan Mohd Razi Idris; Rosazlin Abdullah (Regional Studies in Marine Science, 2026)

SARS-CoV-2 antibody responses during the omicron wave in kano, nigeria: Implications for strengthening future vaccine strategies - Bilkisu Ahmed; Jamilu Abubakar Bala; Taysir Ramadan Hafiz; Isah Abubakar Aliyu; Abdulhadi Sale Kumurya; Ibrahim Muhammad Badamasi; Hayatu Saidu; Muhammad Adamu Abbas; Auwal Idris Kabuga; Alhassan Sharif Abdullahi; Bashiru Garba; Al-Mukhtar Yahuza Adamu; et al. (Next Research, 2026)

Metabolomic insights into gut–brain axis dysregulation under unpredictable chronic stress in zebrafish - Zhang Yizhu; Zaynab Mando; Zenab Aldurrah; Roziana Mohamed Hanaphi; Ahmad Syahir Abd Halim Hapiz; Muhammad Ariff Azmi; Adriana Sofia Abdul Latip; Sarah Idris; Azira Muhamad; Fauziahanim Zakaria (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Morphometric patterns and potential plastic responses of the coral Echinopora spp. along turbidity gradients - Muhammad Irsyad Abiyusfi Ghafari; Mohd Hanafi Idris; Ezmahamrul Afreen Awalludin; Abu Hena Mustafa Kamal (Marine Biology, 2026)

The potential of banana extract and light quality using LEDs to optimize in vitro growth of Paphiopedilum glaucophyllum J.J. Sm. - Tatu Mutiara Syifa; Reni Indrayanti; Popi Aprilianti; Elizabeth Handini; Muhammad Idris; Nunung (In Vitro Cellular & Developmental Biology - Plant, 2026)

A review on the earth observation techniques for coastal vulnerability index in Malaysia - Shin Yi Chen; Nurul Hazrina Idris; Mohammad Hanif Hamden; Amalina Izzati Abdul Hamid; Muhammad Faiz Pa’suya; Norhadija Darwin (International Journal of Remote Sensing, 2026)

Development and validation of SR-DISVAXFIC: A mobile phone application for estimating the herd-level financial impact of small ruminant diseases and the potential benefits of vaccination in the field - Megan E. Rawlins; Adeyinka J. Adedeji; Victoria I. Ifende; Sandra I. Ijoma; Rebecca B. Atai; Joel Y. Atuman; Gambo Panzam; Haruna W. Gotom; Idris H. Adamu; Anas U. Musa; Isa M. Sani; Paul Adamu; et al. (Preventive Veterinary Medicine, 2026)

Macroscale spatiotemporal variability of Beryllium-7 and Lead-212 in surface air driven by meteorological factors - Faisal Izwan Abdul Rashid; Mohd Idzat Idris; Irman Abdul Rahman; Muhammad Rawi Mohamed Zin (Environmental Research, 2026)

Integration of deep learning with superpixel segmentation for automated assessment of building damage following disasters: a case study of port of Beirut explosion - Mothana Alkarkhi; Nurul Hazrina Idris; Muhammad Zulkarnain Abd Rahman (International Journal of Remote Sensing, 2025)

Microbial Proteases: Integration into Food Products and Industrial Processes - Gad Elsayed Mohamed Salem; Muhammad Arif; Imad A. Idris; Mohamed A. El-Sakhawy; Suchana Chavanich; Waleed Alahmad; Yuanzhang Zheng; El-Sayed Salama (Current Microbiology, 2025)

Tritrophic interaction between predator, Verania lineata – pest, Nilaparvata lugens and host plant, Oryza sativa from four provinces in West Sumatra, Indonesia: toward better pest management - My Syahrawati; James Rinaldi; Novri Nelly; Hasmiandy Hamid; Muhammad Afiq Senen; Aqilah Sakinah Badrulisham; Muhamad Ikhwan Idris; Salmah Yaakop (Arthropod-Plant Interactions, 2025)

Advances in bacterial chromium biosorption: current perspectives and future directions - Abdullahi Adamu Faggo; Bashar Haruna Gulumbe; Nazeef Idris Usman; Tirmizhi Munkaila Abubakar; Kadai Alhaji Lawan; Musbahu Abdullahi Bagwai; Kabir Hassan Sambo; Muhammad Bello; Mubarak Hassan Ismail; Wada Nafiu (Environmental Science and Pollution Research, 2025)

Evaluation of Neuroprotective and Neuroregenerative Potential of NeuroAiD™ II(MLC901) in a Rat Model of Kainic Acid-Induced Spinal Cord Injury - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Rashidah Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (Molecular Neurobiology, 2025)
Excitotoxic damage caused by high extracellular levels of glutamate in the spinal cord results in neuronal loss and severe locomotor impairment. This study investigates the efficacy of NeuroAiD II (MLC901), an herbal formulation, in promoting nerve regeneration following spinal cord injury (SCI) induced by kainic acid (KA). KA, a potent glutamate receptor agonist, causes excitotoxic damage in the spinal cord, leading to neuronal loss and locomotor impairment. To explore the potential of MLC901, KA-injured rats were treated with MLC901, and nerve regeneration was evaluated using various techniques. In this study, KA was administered intrathecally between the T12 and T13 vertebrae in rats, resulting in incomplete paraplegia. MLC901 was then tested for its neuro-regenerative potential. Various assessments were conducted to evaluate the effects of MLC901 treatment, including behavioral, electrophysiological, and histopathological analyses. Behavioral tests, such as the Basso, Beattie, and Bresnahan (BBB) open field test, running wheel, grid walk, inverted grid, and sensory tests, showed significant improvements in locomotor activity in treated rats. Electrophysiological recordings indicated that, while KA injection caused reduced amplitude and delayed latency, MLC901 treatment helped restore lost connections on days 14 and 28. Histopathological and immunohistochemical analyses also revealed improved tissue integrity and neuron survival. The study concludes that MLC901 significantly enhances locomotor recovery, somatosensory evoked potentials, and tissue preservation following SCI. These findings suggest that MLC901 holds promise as a neuro-regenerative therapy for spinal cord injuries.

Polymeric carbon nitride-based semiconductors as a beneficial candidate in photocatalysis diversity: A comprehensive review - Sidra Tul Muntaha; Jawad Ali Shah Syed; Muhammad Mateen; Muhammad Ali Shahzad; Anand Parkash; Aqsa Asrar; Adil Emin; Ghulam Abbas Ashraf; Inaam Ullah; Muhammad Ahsan Farooq Qaisar; Salamat Ali; Ahmed Mahmoud Idris (Chemical Engineering Journal, 2025)

Machine learning-based detection and quantification of red blood cells in Cholistani cattle: A pilot study - Sami Ul Rehman; Sania Fayyaz; Muhammad Usman; Mehreen Saleem; Umer Farooq; Asjad Amin; Mushtaq Hussain Lashari; Musadiq Idris; Haroon Rashid; Maryam Chaudhary (Research in Veterinary Science, 2025)

Effect of long-term storage on the quality of cryopreserved sperm of the Pangasius nasutus (Bleeker, 1863) - Nurizzati Idris; Donald Torsabo; Muhammad Yazed Abduh; Ambok Bolong Abol-Munafi; Noordiyana Mat Noordin; Ivan Chong Chu Koh (Cryobiology, 2025)

Evolutionary history of microgastrine wasps (hymenoptera: braconidae: microgastrinae) in Sundaland: insights from Peninsular Malaysia - Ameyra Aman-Zuki; Muhamad Azmi Mohammed; Aqilah Sakinah Badrulisham; Muhammad Ikhwan Idris; Mohd Fuat Salbi; Salmah Yaakop (International Journal of Tropical Insect Science, 2025)

Impact of microplastic exposure on the health of tropical seagrass (Enhalus acoroides) seedlings - Aditya Hikmat Nugraha; Fadhliyah Idris; Tri Apriadi; Carla Dhevanda; Muhammad Yudhistira Azis; Khairul Hafsar (Marine Pollution Bulletin, 2025)

Dynamics of defense-related genes expression in shallot after UV-B-induced resistance against Fusarium acutatum showed time difference - Belinda Winona; Widhi Dyah Sawitri; Muhammad Idris; Valentina D.S. Handayani; Arif Wibowo; Deden D. Matra; Febri Doni; Ani Widiastuti (Physiological and Molecular Plant Pathology, 2025)

In-silico evaluation of Cassia occidentalis phytochemicals for Plasmodium falciparum plasmepsin V inhibition: Revealing antimalarial potential - Aliyu Usman Maaji; Ramgopal Dhakar; Pankaj Kumar Teli; Umesh Garu; Umar Aliyu Adamu; Saminu Saminu Muhammad; Khalipha Ali Jubril; Fatima Idris Sambo (South African Journal of Botany, 2025)

A critical review of NO2 and AOD in major Asian cities: challenges, mitigation approaches and way forwards - Most Mastura Munia Farjana Jion; Abu Reza Md Towfiqul Islam; Mahir Shahrier; Md Yousuf Mia; Jannatun Nahar Jannat; Md Arfan Ali; Md Abdullah Al Masud; Md Firoz Khan; Muhammad Bilal; Abubakr M. Idris; Guilherme Malafaia (Air Quality, Atmosphere & Health, 2025)

Sea-level rise in Southeast Asia: a review of the factors, and the observed rates from tide gauge, satellite altimeters and assimilated data techniques - Nurul Hazrina Idris; Muhammad Haikal Fayyadh Munadi; Chien Zheng Yong; Bing Yu Lee; Stefano Vignudelli (International Journal of Remote Sensing, 2024)

Galactose-1-phosphate uridylyltransferase GalT promotes biofilm formation and enhances UV-B resistance of Bacillus thuringiensis - Aisha Lawan Idris; Xiao Fan; Wen Li; Hankun Pei; Musa Hassan Muhammad; Xiong Guan; Tianpei Huang (World Journal of Microbiology and Biotechnology, 2024)

Variation of micro-morphological features and possible adaptation strategies of platy-laminar corals Echinopora lamellosa and E. pacificus to turbidity stress in changing climate - Muhammad Irsyad Abiyusfi Ghafari; Abu Hena Mustafa Kamal; Mohd Hanafi Idris (Coral Reefs, 2024)

Bacillus spore germination: mechanisms, identification, and antibacterial strategies - Lihua Fan; Yanru Zhang; Balarabe Bilyaminu Ismail; Aliyu Idris Muhammad; Guoliang Li; Donghong Liu (Critical Reviews in Food Science and Nutrition, 2024)

Chromium-extracted aluminum catalyst for co-pyrolysis of cotton fabric waste and polypropylene plastic waste to bio-oil - Nur Alwani Ali Bashah; Muhammad Zahiruddin Ramli; Wan Zuraida Wan Kamis; Siti Shawalliah Idris; Mohamad Anuar Kamaruddin; Ahmad Syahir Zulkipli; Moses Aderemi Olutoye (Journal of Environmental Chemical Engineering, 2024)

Updated review on current approaches and challenges for poly- and perfluoroalkyl substances removal using activated carbon-based adsorbents - Farahin Mohd Jais; Muhammad Shazril Idris Ibrahim; Ahmed El-Shafie; Choe Earn Choong; Minhee Kim; Yeomin Yoon; Min Jang (Journal of Water Process Engineering, 2024)

Development of sperm cryopreservation protocol for patin buah, Pangasius nasutus - Nurizzati Idris; Muhammad Yazed Abduh; Noordiyana Mat Noordin; Ambok Bolong Abol-Munafi; Ivan Chong Chu Koh (Cryobiology, 2024)

Microbiota and soil fauna mediate litter decomposition and associated carbon and nitrogen dynamics in mangrove blue carbon ecosystems: insights from a coastal lagoon in Malaysia - Mohammad Ahsanul Islam; Md Masum Billah; Mohd Hanafi Idris; Wan Mohd Rauhan Wan Hussin; Md Khurshid Alam Bhuiyan; Muhammad Shariefuddin Bin Mohd Sukeri; Abu Hena Mustafa Kamal (Hydrobiologia, 2024)

Mechanical scratch injury on differentiated motor neuron of NSC-34 cells as an in vitro model for evaluation of neuroregeneration potential of NeuroAiD II (MLC901) - Anam Anjum; Muhammad Dain Yazid; Muhammad Fauzi Daud; Jalilah Idris; Angela Min Hwei Ng; Amaramalar Selvi Naicker; Ohnmar Htwe Ismail; Ramesh Kumar Athi Kumar; Yogeswaran Lokanathan (In vitro models, 2024)

Empowering indigenous wisdom: co-creating forest inventory through citizen science in Royal Belum State Park, Malaysia - Mohd Farid Fauzi; Nurul Hawani Idris; Kasturi Devi Kanniah; Mohamad Hafis Izran Ishak; Mohamad Jahidi Osman; Abd Wahid Rasib; Muhammad Zulkarnain Abd Rahman; Alvin Meng Shin Lau (Environment, Development and Sustainability, 2024)

The path of microplastics through the rare biodiversity estuary region of the northern Bay of Bengal - Al-Nure Mubin; Abu Reza Md. Towfiqul Islam; Mehedi Hasan; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; Md. Sha Alam; Md. Refat Jahan Rakib; Muhammad Saiful Islam; Nasima Momtaz; Venkatramanan Senapathi; Abubakr M. Idris; et al. (Journal of Contaminant Hydrology, 2024)

CA/PEG/chitosan membrane incorporated with TiO2 nanoparticles for strengthening and permselectivity membrane for reverse osmosis desalination - Dwiprayogo Wibowo; Faizal Mustapa; S. Selviantori; Muhammad Idris; Amir Mahmud; Maulidiyah Maulidiyah; Muh. Zakir Muzakkar; Akrajas Ali Umar; Muhammad Nurdin (Environmental Nanotechnology, Monitoring & Management, 2023)

Assessing total erythrocyte count as a potential attribute for estimating hemoglobin in Cholistani cattle - Umer Farooq; Musadiq Idris; Nouman Sajjad; Muhammad Abrar Afzal (Tropical Animal Health and Production, 2023)

Synthesis of ethyl levulinate over sulfonated lignin-based carbon catalyst as a fuel additive to biodiesel-diesel blends towards engine emissions - Abdull Hafidz Hassan; Muzakkir Mohammad Zainol; Muhammad Alif Samion; Muhammad A`qil Azlan; Mohd Asmadi; Ahmad Rafizan Mohamad Daud; Idris Saad; Nur Aina Najwa Mohd Nor Azman (Journal of Cleaner Production, 2023)

Vertical electrical sounding for revealing the groundwater resources in the geothermal spring of Jaboi volcano - Muhammad Yanis; Nasrullah Zaini; Faisal Abdullah; Muhammad Isa; Marwan Marwan; Syafrizal Idris; Andri Yadi Paembonan; Riski Ananda; Muzakir Zainal; Azman Abdul Ghani; Deni Saputra (Acta Geophysica, 2023)

The degradation of single-use plastics and commercially viable bioplastics in the environment: A review - Siti Norliyana Idris; Tan Suet May Amelia; Kesaven Bhubalan; Anim Maisara Mohd Lazim; Nurul Aliah Mohd Ahmad Zakwan; Muhammad Imran Jamaluddin; Rameshkumar Santhanam; Al-Ashraf Abdullah Amirul; Sevakumaran Vigneswari; Seeram Ramakrishna (Environmental Research, 2023)

Selection and downscaling of CMIP6 climate models in Northern Nigeria - Idris Muhammad Wada; Haruna Shehu Usman; Amechi S. Nwankwegu; Makhai Nwunuji Usman; Selamawit Haftu Gebresellase (Theoretical and Applied Climatology, 2023)

A window into the future: case study of long-term radiological risk modelling posed by unregulated mining waste repurposing activities - Muhammad Abdullah Rahmat; Aznan Fazli Ismail; Nursyamimi Diyana Rodzi; Eli Syafiqah Aziman; Syazwani Mohd Fadzil; Norsyahidah Mohd Hidzir; Mohd Idzat Idris; Irman Abdul Rahman; Faizal Mohamed (Environmental Monitoring and Assessment, 2023)

An insight into the mechanisms of action of selected bioactive compounds against epigenetic targets of prostate cancer: implications on histones modifications - Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Abdurrahman Pharmacy Yusuf; Yunus Aisha Lawal; Shehu Aisha Jibril; Hussaini Nuraddeen; Musa Mubarak Ibrahim; Idris Zubairu Sadiq; Murtala Bello Abubakar; Ibrahim Malami; Ibrahim Babangida Abubakar; Aliyu Muhammad (In Silico Pharmacology, 2023)

Critical insight into sediment microbial fuel cell: Fundamentals, challenges, and perspectives as a barrier to black-odor water formation - Umar Abdulbaki Danhassan; Hongjian Lin; Ibrahim Lawan; Xin Zhang; Mahmoud H. Ali; Aliyu Idris Muhammad; Kuichuan Sheng (Journal of Environmental Chemical Engineering, 2023)

Mapping Chini Lake (Pahang, Malaysia) using Sentinel-2 images to determine the effect of acid mine drainage in the pre- to post-COVID-19 restriction period - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim (Environmental Monitoring and Assessment, 2023)

The Variation of Riverine Heavy Metal Flux Using RUSLE Model in the Ranau Sub-basins, Malaysia. Adjacent to Ultrabasic Soil - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim (Water, Air, & Soil Pollution, 2022)

A comprehensive review of heavy metal pollution in the coastal areas of Bangladesh: abundance, bioaccumulation, health implications, and challenges - Md.Refat Jahan Rakib; Md. Asrafur Rahman; Amarachi Paschaline Onyena; Rakesh Kumar; Aniruddha Sarker; M. Belal Hossain; Abu Reza Md. Towfiqul Islam; Md. Saiful Islam; Md. Mostafizur Rahman; Yeasmin Nahar Jolly; Abubakr M. Idris; Mir Mohammad Ali; et al. (Environmental Science and Pollution Research, 2022)

Evaluation and selection of CMIP6 climate models in Upper Awash Basin (UBA), Ethiopia - Selamawit Haftu Gebresellase; Zhiyong Wu; Huating Xu; Wada Idris Muhammad (Theoretical and Applied Climatology, 2022)

Changes in air quality during and after large-scale social restriction periods in Jakarta city, Indonesia - Muhammad Rendana; Wan Mohd Razi Idris; Sahibin Abdul Rahim (Acta Geophysica, 2022)

Metabolite profile and gene expression of the roots of oil palm seedlings treated with Hendersonia GanoEF1 and infected with Ganoderma boninense - Muhammad Faiz Ismail; Rosimah Nulit; Idris Abu Seman; Mohd Hafiz Ibrahim; Nurrashyeda Ramli (Journal of Plant Pathology, 2022)

Complete nucleotide sequence of a begomovirus associated with an alphasatellite and a betasatellite naturally infecting okra in Jordan - Nida’ M. Salem; Muhammad Shafiq Shahid; Ali Idris; Dina Hattab; Amany Abdeen (Archives of Virology, 2021)

Indoor transmission dynamics of expired SARS-CoV-2 virus in a model African hospital ward - Jamiu Adetayo Adeniran; Ishaq Alhassan Mohammed; Oladele Idris Muniru; Taofeek Oloyede; Omowonuola Olubukola Sonibare; Muhammad-Najeeb O. Yusuf; Khadijat Abdulkareem Abdulraheem; Emmanuel Tolulope Odediran; Rafiu Olasunkanmi Yusuf; Jacob Ademola Sonibare (Journal of Environmental Health Science and Engineering, 2021)

Tualang honey and its methanolic fraction ameliorate lipopolysaccharide-induced oxidative stress, amyloid deposition and neuronal loss of the rat hippocampus - Wan Muhammad Hilmi Wan Yaacob; Idris Long; Rahimah Zakaria; Zahiruddin Othman (Advances in Traditional Medicine, 2021)

A review of gas chromatographic techniques for identification of aqueous amine degradation products in carbonated environments - Idris Mohamed Saeed; Shaukat Ali Mazari; Peter Alaba; Brahim Si Ali; Badrul Mohamed Jan; Wan Jeffrey Basirun; Yahaya Muhammad Sani; Sabzoi Nizzamuddin; Nabisab Mujawar Mubarak (Environmental Science and Pollution Research, 2021)

Photocatalytic performance improvement by utilizing GO_MWCNTs hybrid solution on sand/ZnO/TiO2-based photocatalysts to degrade methylene blue dye - Nur Jannah Idris; Suriani Abu Bakar; Azmi Mohamed; Muqoyyanah Muqoyyanah; Mohd Hafiz Dzarfan Othman; Mohamad Hafiz Mamat; Mohd Khairul Ahmad; Muhammad Danang Birowosuto; Tetsuo Soga (Environmental Science and Pollution Research, 2021)

In silico predictions on the possible mechanism of action of selected bioactive compounds against breast cancer - Aliyu Muhammad; Babangida Sanusi Katsayal; Gilead Ebiegberi Forcados; Ibrahim Malami; Ibrahim Babangida Abubakar; Amina Isah kandi; Adam Muntaka Idris; Sabi’u Yusuf; Salihu Muktar Musa; Nagedu Monday; Zak-wan Sidi Umar (In Silico Pharmacology, 2020)

Ecologically controlling insect and mite pests of tea plants with microbial pesticides: a review - Aisha Lawan Idris; Xiao Fan; Musa Hassan Muhammad; Yachong Guo; Xiong Guan; Tianpei Huang (Archives of Microbiology, 2020)

Bacterial spore inactivation induced by cold plasma - Xinyu Liao; Aliyu Idris Muhammad; Shiguo Chen; Yaqin Hu; Xingqian Ye; Donghong Liu; Tian Ding (Critical Reviews in Food Science and Nutrition, 2019)

Periodic vicissitudes of different concentrations of a developed prototype killed S. aureus mastitis vaccine on immune modulators, mediators and immunoglobulins in cows - Idris Umar Hambali; Faez Firdaus Jesse Bin Abdullah; K. R. Bhutto; M. L. Mohd Azmi; A. H. Wahid; Z. Zakaria; M. N. Odhah; M. Arsalan; N. A. Muhammad; M. N. Jefri (Tropical Animal Health and Production, 2019)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Assessment of groundwater vulnerability to anthropogenic pollution and seawater intrusion in a small tropical island using index-based methods - Nura Umar Kura; Mohammad Firuz Ramli; Shaharin Ibrahim; Wan Nor Azmin Sulaiman; Ahmad Zaharin Aris; Adamu Idris Tanko; Muhammad Amar Zaudi (Environmental Science and Pollution Research, 2015)

Arsenic Toxicity on Ludwigia octovalvis in Spiked Sand - Harmin Sulistiyaning Titah; Siti Rozaimah Sheikh Abdullah; Idris Mushrifah; Nurina Anuar; Hassan Basri; Muhammad Mukhlisin (Bulletin of Environmental Contamination and Toxicology, 2013)